Typicality of functional connectivity robustly captures motion artifacts in rs-fMRI across datasets, atlases, and preprocessing pipelines - Kopal, Jakub; Pidnebesna, Anna; Tomeček, David; Tintěra, Jaroslav; Hlinka, Jaroslav (Human brain mapping, 2020)
Functional connectivity analysis of resting-state fMRI data has recently become one of the most common approaches to characterizing individual brain function. It has been widely suggested that the functional connectivity matrix is a useful approximate representation of the brain's connectivity, potentially providing behaviorally or clinically relevant markers. However, functional connectivity estimates are known to be detrimentally affected by various artifacts, including those due to in-scanner head motion. Moreover, as individual functional connections generally covary only very weakly with head motion estimates, motion influence is difficult to quantify robustly, and prone to be neglected in practice. Although the use of individual estimates of head motion, or group-level correlation of motion and functional connectivity has been suggested, a sufficiently sensitive measure of individual functional connectivity quality has not yet been established. We propose a new intuitive summary index, Typicality of Functional Connectivity, to capture deviations from standard brain functional connectivity patterns. In a resting-state fMRI dataset of 245 healthy subjects, this measure was significantly correlated with individual head motion metrics. The results were further robustly reproduced across atlas granularity, preprocessing options, and other datasets, including 1,081 subjects from the Human Connectome Project. In principle, Typicality of Functional Connectivity should be sensitive also to other types of artifacts, processing errors, and possibly also brain pathology, allowing extensive use in data quality screening and quantification in functional connectivity studies as well as methodological investigations.
Keywords: hlava - pohyby; rs-fMRI; Connectome; konektom; počítačové zpracování obrazu; datové soubory jako téma; mužské pohlaví; mozek; Head Movements; Adult; mladý dospělý; quality; atlasy jako téma; magnetická rezonanční tomografie; Artifacts; Magnetic Resonance Imaging; Brain; Young Adult; ženské pohlaví; Atlases as Topic; Humans; artefakty; Datasets as Topic; Image Processing, Computer-Assisted; functional connectivity; atlas; dospělí; motion; Female; lidé; Male